Selecting soluble/foldable protein domains through single‐gene or genomic ORF filtering: structure of the head domain of Burkholderia pseudomallei antigen BPSL2063. (1st November 2015) - Gourlay, Louise J.; Peano, Clelia; Deantonio, Cecilia; Perletti, Lucia; Pietrelli, Alessandro; Villa, Riccardo; Matterazzo, Elena; Lassaux, Patricia; Santoro, Claudio; Puccio, Simone; Sblattero, Daniele; Bolognesi, Martino
Abstract : The 1.8 Å resolution crystal structure of a conserved domain of the potential Burkholderia pseudomallei antigen and trimeric autotransporter BPSL2063 is presented as a structural vaccinology target for melioidosis vaccine development. Since BPSL2063 (1090 amino acids) hosts only one conserved domain, and the expression/purification of the full‐length protein proved to be problematic, a domain‐filtering library was generated using β‐lactamase as a reporter gene to select further BPSL2063 domains. As a result, two domains (D1 and D2) were identified and produced in soluble form in Escherichia coli . Furthermore, as a general tool, a genomic open reading frame‐filtering library from the B. pseudomallei genome was also constructed to facilitate the selection of domain boundaries from the entire ORFeome. Such an approach allowed the selection of three potential protein antigens that were also produced in soluble form. The results imply the further development of ORF‐filtering methods as a tool in protein‐based research to improve the selection and production of soluble proteins or domains for downstream applications such as X‐ray crystallography.